The Effect Of PPKN Learning On Knowledge Of National Insights Of Students Of MTS Miftahul Huda Ukui District - Pipit Wulandari, Ahmad Eddison, Supentri (Pusdikra Publishing, 2022)
This research is motivated by the real situation at MTs Miftahul Huda, Ukui District regarding the existence of problems regarding knowledge of national insight. The formulation of the problem in this study is whether there is an effect of Civics learning on the knowledge of students' national insight at MTs Miftahul Huda, Ukui District. The purpose of the study was to determine whether there was an effect of Civics learning on students' national insight knowledge at MTs Miftahul Huda, Ukui District. The benefits of research, hopefully with this research the authors hope that it can help become a source of knowledge and contribute to the world of education related to writing scientific papers about the influence of Civics learning on students' national insight knowledge at school. This research method is descriptive quantitative, data collection instrument using a questionnaire consisting of 38 questions. The population in this study were students of MTs Miftahul Huda, Ukui District, totaling 78 people consisting of grades VII, VIII and IX, with the sampling using the total sampling technique. Based on the results of the study, there is a positive influence between Civics learning on knowledge of national insight. This can be proven by a simple linear regression analysis using the SPSS application, namely = 34.026 + 0.780 X. The results of the above equation can be translated as a constant of 34.026 which means that the value of the consistency of the PPKn Learning variable is 34, 026 the regression coefficient of X is 0.780 which states that the addition 1% of the value of Civics learning, the knowledge of students' national insight will increase by 0.780. This coefficient is positive, meaning that Civics learning (X) has a positive effect on students' national insight knowledge (Y).